Distribution, abundance, and risk assessment of selected antibiotics in a shallow freshwater body used for drinking water, China. (15th February 2021) - Kong, Ming; Bu, Yuan-Qing; Zhang, Qin; Zhang, Sheng-Hu; Xing, Li-Qun; Gao, Zhan-Qi; Bi, Feng-Zhi; Hu, Guan-Jiu
Abstract: With rapid improvements in industrialization and urbanization, antibiotics are now extensively used to prevent and treat human and animal diseases and husbandry and aquaculture. Some research has been conducted to assess the environmental distribution and risk level of antibiotics, but their distribution remains largely uncharacterized. Thus, this study investigated the distribution and abundance of 39 antibiotics belonging to five groups, and their associated risks in surface water around Luoma Lake in the north of Jiangsu province, China. Nineteen antibiotics were detected, at a detection frequency (DF) ranging from 2.27% to 100%. The total antibiotics (ΣABs) concentrations ranged from 34.91 to 825.93 ng/L, with a median concentration of 195.45 ng/L. Among these antibiotics, chlortetracycline (DF: 100%; median: 172.02 ng/L) was the dominant antibiotic, accounting for a median percentage of 91.0% of ΣABs concentrations. Spearman rank correlation method found a significant correlation between clindamycin (DF: 72.7%; median: 2.01 ng/L) and lincomycin (DF: 79.5%; median: 4.58 ng/L). The ecological risk quotient (RQ) values for two out of 44 sampling sites were higher than 1, indicating a high risk; 11.4% of the RQ values fell between 0.1 and 1, indicating a medium risk. Moreover, roxithromycin was found to be the dominant contributor to the ecological risk, accounting for a median of 79.7% of ΣABs. However, the total non-carcinogenic (<6.54 × 10 −4 ) and carcinogenic risks (<1.64 × 10 −7 ) of ΣABs were negligible at the detected concentrations. Graphical abstract: Image 1 Highlights: Concentrations and distributions of 39 antibiotics around Luoma Lake were revealed. Chlortetracyclin was found to be the dominant antibiotic, with a median of 172.02 ng/L. Ecological risks of antibiotics were at medium level (11.4%) or slightly high level (4.6%). Non-carcinogenic and carcinogenic risks of antibiotics were low at the detected concentrations.